Role of ferroptosis in the pathogenesis of heart disease - Fatima, Sulail; Zhou, Haiyan; Chen, Yi; Liu, Qinghang (Frontiers in Physiology, 2024)
Ferroptosis is a new form of regulated necrosis characterized by iron-dependent lipid peroxidation, leading to irreparable lipid damage, membrane permeabilization, and necrotic cell death. Ferroptosis has recently been implicated in the pathogenesis of multiple forms of heart disease such as myocardial infarction, cardiac hypertrophy, heart failure, and various cardiomyopathies. Important progress has also been made regarding how ferroptosis is regulated in vitro and in vivo as well as its role in cardiac homeostasis and disease pathogenesis. In this review, we discuss molecular mechanisms that regulates ferroptosis in the heart, including pathways leading to iron overload and lipid peroxidation as well as the roles of key organelles in this process. We also discuss recent findings pertaining to the new pathogenic role of ferroptosis in various forms of heart disease as well as genetic and pharmacologic strategies targeting ferroptosis in the heart.